Microorganisms associated with the production of volatile compounds in spoilt tomatoes - A.D., Ibrahim; Musa, K.; Sani, A.; Aliero, A.A.; B. S., Yusuf (Research in Biotechnology, 2011)
The microorganisms associated with the production of volatile compounds in spoilt tomatoes has been isolated and identified. The mean heterotrophic bacterial count recorded range between 8.7 x 106 to 9.1 x 106 cfu/g. The highest value was obtained from Bado and the least from Dundaye market. The organisms isolated and identified include three species of bacteria and four fungal species. These include Bacillus, Listeria, Morganella, Aspergillus, Absidia, and Fusarium. GC-MS analysis revealed the presence of eight compounds dominated by 9, 12 – octadecadienoic acid (31.08%), 2, 3 – Butandiol (28.79%), and n-Hexadecanoic acid (19.85%). This study suggests that spoilt tomatoes could be exploited for the biogeneration of some volatile compounds that could provide baseline knowledge for curbing post harvest lost.